Role Play Methods Strategies to Improve Students' Speaking Ability: English - M. Hilmy Hidayatullah; Sirrul Bari; Annisa Kurnia Asri; Nur lailiyatul Janna (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
This study aimed to determine the implementation of role play to improve students’ speaking skill in the grade VIII MTs Al-Ittihad Ketupat Ra’as Sumenep. This research used Classroom Action Research (CAR) which consisted of two cycles, each cycle included planning, implementing, observing, and reflecting. The cycle was stopped when the indicators of success had achieved the completeness of learning set by the school. Completeness of learning for grade VIII subjects is 75%. The results showed students’ increase in the grade VIII MTs Al-Ittihad Ketupat Ra’as Sumenep learning outcomes in each cycle. The increase in learning outcomes was shown in the pre-test results with the percentage of completeness of learning 4,55% and there was an increase in the results of the post-test cycle 1 to 31,82%, and an increase again in the results of the post test cycle 2 to 81,82%. The increase in learning outcomes from the results of the pre-test, post-test cycle I to post-test cycle II was due to improvements in the application of role play after evaluating the learning process activities and learning outcomes. From the results of observations in the learning process of students’ speaking skill in the grade VIII MTs Al-Ittihad Ketupat Ra’as Sumenep, the students showed a good response. It could be concluded that learning using role play strategy in the grade VIII MTs Al-Ittihad Ketupat Ra’as Sumenep could improve the student’s speaking skill.